Financial Statement Model Based on SAK EMKM In The “Polife” Student Entrepreneur Group - Kumaat, Lusye Corvanty; Paendong, Yelly Sjenny; Lintong, Jerry Sonny (Future Science, 2021)
The purpose of this research is to create a Financial Report Model based on SAK-EMKM in the Student Entrepreneurial Group